Short stop mediates axonal compartmentalization of mucin-type core 1 glycans - Kinoshita, Takaaki (Sci Rep, 2017)
T antigen, mucin-type core 1 O-glycan, is highly expressed in the embryonic central nervous system (CNS) and co-localizes with a Drosophila CNS marker, BP102 antigen. BP102 antigen and Derailed, an axon guidance receptor, are localized specifically in the proximal axon segment of isolated primary cultured neurons, and their mobility is restricted at the intra-axonal boundary by a diffusion barrier. However, the preferred trafficking mechanism remains unknown. In this study, the major O-glycan T antigen was found to localize within the proximal compartments of primary cultured Drosophila neurons, whereas the N-glycan HRP antigen was not. Ultrastructural analysis by atmospheric scanning electron microscopy revealed that microtubule bundles cross one another at the intra-axonal boundary, and that T antigens form circular pattern before the boundary. We then identified Short stop (Shot), a crosslinker protein between F-actin and microtubules, as a mediator for the proximal localization of T antigens; null mutation of shot cancelled preferential localization of T antigens. Moreover, F-actin binding domain of Shot was required for their proximal localization. Together, our results allow us to propose a novel trafficking pathway where Shot crosslinks F-actin and microtubules around the intra-axonal boundary, directing T antigen-carrying vesicles toward the proximal plasma membrane.